Developing Instructional Instruments Based on The Local Wisdom of Osingese Society’s of Banyuwangi Through Guided Discovery to Enhance The Students Mathematical Communication Ability (International Journal of Scientific Research and Management (IJSRM), 2017)
Mathematical communication is an important ability to be mastered by students and developed in the world of education because the ability of mathematical communication is prevalently required. Mastering the ability, students are able to represent and solve various mathematical problems both in learning Mmathematics and in everyday life. In the current implementation of 2013 curriculum, the existence of innovative and creative learning instruments need to be developed in order to enable students to communicate mathematical ideas and construct their own concept or knowledge based on their own experiences. The purposes of this research are (1) to describe the process and result of development of instructional instrument in the form of lesson plan, worksheet, and learning achievement test based on local wisdom of Osingese Banyuwangi society through guided discovery model; (2) to describe students’ mathematical communication ability on topic pertinent to trapezium. The present study applied research and development method, using modification of 4-D development model through four stages, inter alia: defining, designing, developing, and developing. Subjects in this study were teachers and students of grade VII-D at The Public Junior High School 2 of Genteng. The results of the research evinced that (1) learning instruments based on local wisdom of Osingese Banyuwangi Society;s through guided discovery model were proven valid, practical and effective by validators and (2) that students’ mathematical communication ability on topic concerned with ​​trapezium was improved after using the developed instructional instrument.